Inbreeding depression from selfing and mating between relatives in the Neotropical tree Cariniana legalis Mart. Kuntze - Tambarussi, E; Boshier, D; Vencovsky, R; Menezes Freitas, L; Sebbenn, A (Springer Verlag, 2016)
Selfing or mating between related individuals in self-compatible hermaphroditic tree species may lead to inbreeding depression (ID) due to homozygosis in recessive, identical by descent alleles. In general, studies of ID in tree species have been based on comparisons of selfed individuals (produced by controlled pollination) with outcrossed individuals for quantitative traits in progeny tests. However, this approach requires a long time to quantify the extent of ID. Thus, we used an approach based on genetic markers to estimate coancestry coefficients between assigned parents from paternity analysis in two populations of the Neotropical tree Cariniana legalis. Using this method, we were able to determine which seedlings in a nursery trial originated from; i) outcrossing between un-related trees, ii) mating between related trees and iii) selfing. We detected a low selfing rate (< 10%), but a substantial quantity of seedlings from mating between related parents (minimum of 35.7%). In general, the outcrossed seedlings from unrelated parents exhibited significantly greater genetic diversity than those resulting from selfing and mating among relatives. The extent of ID varied among traits and populations. Outcrossed seedlings originating from unrelated trees generally showed greater survival than seedlings originating from selfing and related parents. Inbreeding depression was greater in the selfed seedlings than in those from mating among related parents. The results are discussed in terms of implications for genetic conservation, breeding and environmental restoration using the species.